Multi-Walled Carbon Nanotubes Effect on Plant and Microbial Growth - Keita, Kadiatou; Okafor, Florence (New Visions in Biological Science Vol. 3, 2021)
Carbon nanotubes, made of graphene, one of the world’s strongest material, has shown properties that are used in applications such as energy storage devices, electron emission devices, and environmental engineering application. Recently, researchers have focused on determining the effects of carbon nanotubes on soil microorganisms and plants. Objective: The purpose of this study was to determine if the multi-walled carbon nanotubes will affect the growth of Phaseolus vulgaris as well as inhibit the growth of select soil microbes. Methods: The effects of Multi-Walled Carbon Nanotubes were determined on bean plants grown under hydroponic conditions and on select soil microbes. Two weeks after germination, the plants were exposed to different concentrations of dispersed multi-walled carbon. The different concentrations were 0 ug (control), 50 \(μ\)g, 250 \(μ\)g, 500 \(μ\)g, 750 \(μ\)g and 1000 \(μ\)g mL- 50 \(μ\)g, 250 \(μ\)g, 500 \(μ\)g, 750 \(μ\)g and 1000 \(μ\)g mL-1. The growth was reported weekly by measuring the plants themselves, the diameter of the leaf, length and width, the roots, and the fruits. Cultures of Mesorhizobium sp. and Nitrosomonas stercoris were exposed to the 0ug (control), 50 \(μ\)g, 250 \(μ\)g, 500 \(μ\)g, 750 \(μ\)g and 1000 \(μ\)g mL-1 of dispersed MWCNTs then incubated in the BioScreen reader. The optical density was reported every 30 minutes for 24 hours. Results: Our results showed that at 50 \(μ\)g/mL, bean plants exhibited tolerance to the multi-walled carbon nanotubes whereas at 250 \(μ\)g/mL and 500 \(μ\)g/mL of MWCNTs plants showed reduced growth and development and even plant death. Aliquots of 750 \(μ\)g/mL and above of MWCNTs lowered the microbial biomass. The presence of high concentrations of carbon nanotubes is likely to cause stress to microbes and the direct contact of CNTs with microbes could damage their cell membrane leading to cell death. Conclusion: As results of this study, the concentration of multi-walled carbon nanotubes should be set at a maximum of 500 \(μ\)g mL-1 when being released to the soil or environment.